Implementasi Pembelajaran Berbasis Quizizz sebagai Asesmen Pembelajaran IPS pada Kelas 5 SDN Sungai Lumbah 1 Barito Kuala - Norlia Ismiyanti; Sherly Radhika Kencana; Putri Andini; Aldi Ferdiyansyah; Asniwati Asniwati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The problem experienced by teachers is that teachers have limitations in conducting assessments during learning due to the lack of teacher insight in accessing creative and interactive assessment support applications by utilizing technology. The main problem in learning based on LCD projector technology in schools is the incompatibility between innovative learning methods and assessments that are still commonplace. The purpose of this study was to analyze the implementation of interactive assessments based on quizizz. The type of research is descriptive qualitative, the research subjects are homeroom teachers and students. Data collection methods through observation, interviews, documentation of learning outcomes, recordings of the learning process, journals and books. The results of the study showed that there was an assessment of the development of elementary school children's learning. The results of the study showed a significant positive influence from the use of quizizz on increasing learning motivation and achieving minimum student competencies. The impact after the evaluation activity of using the quizizz paper mode application was carried out increased student learning motivation and student participation during the activity.